2018
DOI: 10.1016/j.clinbiomech.2018.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the primary stability of standard vs lateralised cementless femoral stems – A finite element study using a diverse patient cohort

Abstract: Findings of this study suggest that, with the appropriate size and alignment, the standard offset design is likely to be sufficient for primary stability, in most cases. Nonetheless, appropriate use of lateralised stems has the potential reduce the risk of peri-prosthetic bone damage. This highlights the importance of appropriate implant selection during the surgical planning stage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 46 publications
(65 reference statements)
0
6
0
Order By: Relevance
“…Peak micromotions in the femoral stem/bone interface typically occur in the posteromedial region during activities of daily living. Al‐Dirini et al 34 conducted a FEA on a cohort of 31 femora to investigate the femoral micromotions for standard, lateral and coxa vara stem configurations for walking and stair climbing, recording the highest peak and median micromotions during both activities for the lateral stem configuration. Abdul Kadir et al 4 showed with a FEA model correlated to an in vitro micromotion experiment on four cadavers that an interference fit around 50 µm in the FEA model corresponds most closely to the situation of a press‐fit of an uncemented stem and reported micromotions in the upper stem zone of 50–150 µm.…”
Section: Discussionmentioning
confidence: 99%
“…Peak micromotions in the femoral stem/bone interface typically occur in the posteromedial region during activities of daily living. Al‐Dirini et al 34 conducted a FEA on a cohort of 31 femora to investigate the femoral micromotions for standard, lateral and coxa vara stem configurations for walking and stair climbing, recording the highest peak and median micromotions during both activities for the lateral stem configuration. Abdul Kadir et al 4 showed with a FEA model correlated to an in vitro micromotion experiment on four cadavers that an interference fit around 50 µm in the FEA model corresponds most closely to the situation of a press‐fit of an uncemented stem and reported micromotions in the upper stem zone of 50–150 µm.…”
Section: Discussionmentioning
confidence: 99%
“…Published population level studies have paved the way for ISCT by demonstrating the technical feasibility to study a specific patient risk on a large number of virtual patients. 1 , 2 , 12 , 31 , 38 , 40 , 44 These analyses generally considered one failure mode in complete isolation; however, clinical studies encompass the large number of patient risks that reflect the total performance of the medical device. Determination of the potential patient risks in scope of an ISCT is necessary to ensure the device performance is sufficiently addressed while maximizing the utility of the ISCT.…”
Section: Barriers To Isct Applicationsmentioning
confidence: 99%
“…27 , 42 , 47 , 48 Published population level studies have demonstrated the technical feasibility to assess a specific patient risk on a large number of virtual patients. 1 , 2 , 12 , 31 , 38 , 40 , 44 Further, regulators are increasingly open to use of computer-generated evidence. 46 , 47 ISCT has therefore the potential to become a new viable source for credible data on clinical device performance (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Primary stability and stress shielding of a select few, mostly esoteric, THA femoral stem designs have been investigated using FEA. [11][12][13][14][15][16] To our knowledge, FEA has not previously been utilised to study the more clinically impactful issue of periprosthetic fracture risk as it varies widely across implanted femoral stem designs.…”
Section: Introductionmentioning
confidence: 99%